Digital Watermarking Techniques - Chahal, Prabhjot Kaur; Singh, Amritpal; Singh, Palwinder (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
More the development of the multimedia, more the digitalization, the more is the access to internet. This fast rate of enhancement gives a sense of protection and authentication.Â Digital watermarking technology provides a strong solution to insecurity created by digitalization. In this paper, our focus is on the basic concepts of watermarking, their characterisation, their techniques. Extending more, we will elaborate one of the latest technique of watermarking named as â€œDiscrete Cosine Transformâ€ (DCT).